Determinants of The Application of Macro Prudential Instruments - Zakaria, Firano; Fatine, Filali A. (Comparative Economic Research. Central and Eastern Europe, 2017)
The use of macro prudential instruments today gives rise to a major debate within the walls of central banks and other authorities in charge of financial stability. Contrary to micro prudential instruments, whose effects remain limited, macro prudential instruments are different in nature and can affect the stability of the financial system. By influencing the financial cycle and the financial structure of financial institutions, the use of such instruments should be conducted with great vigilance as well as macroeconomic and financial expertise. But the experiences of central banks in this area are sketchy, and only some emerging countries have experience using these types of instruments in different ways. This paper presents an analysis of instruments of macro prudential policy and attempts to empirically demonstrate that these instruments should be used only in specific economic and financial situations. Indeed, the results obtained, using modeling bivariate panel, confirm that these instruments are more effective when used to mitigate the euphoria of financial and economic cycles. In this sense, the output gap, describing the economic cycle, and the Z-score are the intermediate variables for the activation of capital instruments. Moreover, the liquidity ratio and changes in bank profitability are the two early warning indicators for activation of liquidity instruments.